An anti‐hair loss treatment in the management of mild androgenetic alopecia: Results from a large, international observational study. Issue 6 (22nd October 2021) - Reygagne, Pascal; Mandel, Victor Desmond; Delva, Catherine; Havlíčková, Michaela; Padlewska, Kamila; Khalil, Rose; Meuleman, Veronique; Miranda, Gilberto Adame; Nevskaya, Mariya; Michelet, Jean‐Francois; Pouradier, Florence; Vano‐Galvan, Sergio; et al.
Abstract: Androgenic alopecia (AGA) is a common and chronic condition. It may impact self‐esteem, self‐image and quality of life. Benefit, tolerability, cosmetic acceptance and patient satisfaction are key to ensure good treatment outcome. Hair loss improvement and hair quality with AC5 (2, 4‐Diamino‐Pyrimidine‐N‐Oxyde, arginine, 6‐O glucose linoleate (SP94), piroctone olamine and Vichy mineralizing water) once daily was assessed in 527 subjects with mild AGA in an open‐label, observational, international real‐life study. After 3 months, investigators evaluated the impact of AC5 on hair loss, product satisfaction and asked subjects about local tolerance; subjects assessed hair growth and quality and satisfaction. Data from 357 subjects were evaluable for the benefit analysis; 59.9% of subjects were female; the mean age was 33.6±8.7 years. Duration of hair loss was 1.62±2.24 years. 71.3% of women had a Ludwig score of 1 and 40.8% of men had a Hamilton Norwood score of 2. At the end of study, hair loss was reduced in 89.0% of subjects; it was slightly higher in women (92.5%) than in men (83.8%). Subject satisfaction on a scale from 0 (not satisfied at all) to 10 (completely satisfied) was 7.9±1.7. Tolerance was rated good to very good by 98.6% of all subjects. In conclusion, AC5 reduces mild AGA in both men and women with a pleasant texture. AC5 was well tolerated and highly appreciated.